2022
DOI: 10.1007/s11104-021-05285-1
|View full text |Cite
|
Sign up to set email alerts
|

Role of nanosilicab to boost the activities of metabolites in Triticum aestivum facing drought stress

Abstract: Drought stress is a threat to agriculture which is decreasing the yield of crops and creating a considerable loss. This research focused on the part played by silicon dioxide nanoparticles (SiO 2 NPs), biofertilizers, and nanosilicab on Triticum aestivum under control and drought stress. Nanosilicab enhanced the germination percentage, germination index, and germination vigor index by 23.07%, 14.49% and, 93.10% under control and 14.42%, 10.52%, and 46.15% under drought. In the pot experiment, the soil was trea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 96 publications
(62 reference statements)
2
8
0
Order By: Relevance
“…Recent studies have shown that Si‐based NMs modulate the effect of ABA on plants. For example, soil exposure to 150 mg/kg SiO 2 NPs significantly reduced the ABA content by 44.1% in wheat ( Triticum aestivum L.) as compared to the control 53 . Similar findings were reported with 100 mg/L SiO 2 NP‐treated cotton 33 .…”
Section: Resultssupporting
confidence: 73%
See 1 more Smart Citation
“…Recent studies have shown that Si‐based NMs modulate the effect of ABA on plants. For example, soil exposure to 150 mg/kg SiO 2 NPs significantly reduced the ABA content by 44.1% in wheat ( Triticum aestivum L.) as compared to the control 53 . Similar findings were reported with 100 mg/L SiO 2 NP‐treated cotton 33 .…”
Section: Resultssupporting
confidence: 73%
“…For example, soil exposure to 150 mg/kg SiO 2 NPs significantly reduced the ABA content by 44.1% in wheat (Triticum aestivum L.) as compared to the control. 53 Similar findings were reported with 100 mg/L SiO 2 NP-treated cotton. 33 In addition, GA 3 can positively regulate plant growth.…”
Section: Phytohormone Crosstalksupporting
confidence: 78%
“…Nanobiofertilizer has been prepared in Iran, and its application increased the amount of proline, carbohydrate, and anthocyanin in Hibiscus sabdariffa [ 124 ] and Foeniculum vulgare [ 144 ] under drought stress [ 145 ]. Jahangir et al [ 125 ] carried out their experiments in Pakistan to show that the combined application of PGPR and Ag NPs increases the weight of Allium cepa facing high salinity. They also reported that the co-application increased the sugar content and the expression of some new proteins in plants.…”
Section: Current Scenario Of Nanobiofertilizer Research and Applicationsmentioning
confidence: 99%
“…Si is beneficial for the growth, development, and yield of many plant species [ 17 ]. The positive effects of Si applications have been reported, including improvements in the intensity of the physiological and metabolic processes [ 18 , 19 ], an increased insect and disease resistance [ 20 ], an improvement in the nutrient imbalance [ 21 ], and an improved tolerance to salt [ 22 ] and droughts [ 23 , 24 ]. In response to droughts, plants stimulate the production of reactive oxygen species (ROS), which causes membrane injuries, protein degradation, and enzyme inactivation, therefore triggering oxidative stress [ 25 ].…”
Section: Introductionmentioning
confidence: 99%